Comparison Of Open and Laparoscopic Prosthetic Repair of Large Ventral Hernias - Pratik H Vyas; Amit H Joshi; Amit H Joshi; Nayan Odedra; Kush S Shah (Medsci Publications, 2016)
Introduction: Open ventral hernia repair is associated with significant morbidity and high recurrence rates. Recently, the laparoscopic approach has evolved as an attractive alternative. Our objective was to compare open with laparoscopic ventral hernia repairs. Methods: 50 laparoscopic and 22 open ventral hernia repairs were included in the study. All patients underwent a tension-free repair with retro muscular placement of the prosthesis. Results: No significant difference was found in the operative time between the 2 groups (laparoscopic 132.7 min vs open 152.7 min). Laparoscopic repair was associated with a significant reduction in the postoperative narcotic requirements (P<0.002); the lengths of nothing by mouth (NPO) status (P<0.001); and hospital stay (P<0.001). The incidence of major complications (P<0.028); the hernia recurrence (P<0.028); and the time required for return to work (P<0.036) were significantly reduced in laparoscopic group. Conclusions: Laparoscopic ventral hernioplasty offers significant advantages and should be considered for repair of primary and incisional ventral hernias.